2018
DOI: 10.17921/2447-8938.2018v20n4p238-242
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Remineralizing Dentifrice in the Treatment of Erosive Enamel Lesions

Abstract: O objetivo deste trabalho in vitro foi avaliar a influência de diferentes agentes remineralizantes no tratamento de lesões erosivas em esmalte. Foram confeccionados espécimes de 4mmx4mm e 3 mm de espessura a partir da superfície vestibular de incisivos bovinos (n=10) e divididos aleatoriamente em 4 grupos. G1=aplicação do dentifrício remineralizante, G2= aplicação do agente potencializador remineralizante, G3= dentifrício remineralizante + agente potencializador remineralizante, G4=aplicação de verniz fluoreta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…14 In addition, bovine incisors are frequently used in dental research due to the difficult to obtain intact human teeth, 15 and its larger surface allow the use of demineralization and remineralization researches. 5,6,8,16,17 In this study it was observed that there was no significant difference in statistical values between the groups of the control region, that indicates that the waterproofing of the specimens with the nail enamel and sticky wax was effective (Table 1). However, in the experimental region of the specimens the values of surface roughness presented statistical similar values between the groups and statistically higher when compared with that obtained at the control region ( Table 1).…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…14 In addition, bovine incisors are frequently used in dental research due to the difficult to obtain intact human teeth, 15 and its larger surface allow the use of demineralization and remineralization researches. 5,6,8,16,17 In this study it was observed that there was no significant difference in statistical values between the groups of the control region, that indicates that the waterproofing of the specimens with the nail enamel and sticky wax was effective (Table 1). However, in the experimental region of the specimens the values of surface roughness presented statistical similar values between the groups and statistically higher when compared with that obtained at the control region ( Table 1).…”
Section: Resultsmentioning
confidence: 63%
“…7 Fluoride compounds are effective in dental remineralization increasing tooth acid resistance after an acid challenge 8 because in high Influence of Remineralizing Agents on the Surface Roughness of Eroded Dental Enamel: in Vitro Study concentrations they promote the precipitation of a calcium fluoride layer in the enamel 9 that acts as a barrier on this surface, acting as a fluoride reservoir inhibiting contact of the acids with the dental surface. 8,[10][11][12][13] Furthermore, the use of a calcium silicate and sodium phosphate-based toothpaste presented great results as a treatment to erosive dental lesions because its regular use can promote mineral regeneration at the enamel surface. 8 Thus, the present study analyzed the influence of different remineralizing agents on the treatment of acid erosion in dental enamel by the evaluation of surface roughness (µm 2 ) with confocal laser scanning microscopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluoride-containing formulations, such as sodium fluoride, have been extensively studied as an anti-erosive agent. In high concentrations, they promote the precipitation of a calcium fluoride layer in the enamel that acts as a fluoride reservoir and reduces the dissolution of enamel exposed to acids 16 . The use of calcium silicate and sodium phosphate-based compounds, such as casein phosphopetides and amorphous calcium phosphates, has also been proposed 17 .…”
Section: Introductionmentioning
confidence: 99%